Building the evidence base for waterpipe regulation and policy. (25th November 2019) - Maziak, Wasim; Sharma, Eva
Abstract : Waterpipe (hookah, shisha, narghileh) smoking is emerging as an epidemic, particularly among young people in the USA and globally. Unlike cigarettes, waterpipe smoking involves several components (eg, tobacco, charcoal, device and venues) and is characterised by unique smoking patterns that expose smokers to significant amounts of nicotine and other toxic substances. With the rising prevalence of use among young people and continuing misperceptions about waterpipe's harmful nature, a better understanding of health risks associated with waterpipe smoking is warranted. In response to waterpipe's rising trends, a Deeming Rule that extended the US Food and Drug Administration's (FDA) regulatory authority to all tobacco products was issued in 2016. This rule includes waterpipe tobacco, components and parts. This development created the need for evidence to guide the FDA into best evidence-based strategies to limit waterpipe's spread among young people and harm to public health. This special issue presents some of the studies that were funded under the 'Chemistry, Toxicology, and Addiction Research on Waterpipe Tobacco' programme to inform promising regulatory action on waterpipe products. In this preamble, we briefly summarise findings from these studies and discusses their policy and regulatory implications for different waterpipe products and components.